Perceived Barriers of Tuberculosis Case Notification among Private Practitioners in Central Karnataka - Satish Ghatage; Anurupa MS; Swathi Aithal (National Journal of Community Medicine, 2021)
Background: India is the highest tuberculosis (TB) burden country in the world accounting for almost one-fourth of the global cases and deaths as per the global TB report 2021. There are evidences suggesting that private practitioners (PPs) in India are not equipped with sufficient knowledge to carry out proper management of TB patients and certain barriers in TB case notification. So the present study is under taken to explore the perceived barriers for TB case notification from private practitioners.